Will automation and robotics lead to more inequality? - Elise S. Brezis; Amir Rubin (Bar-Ilan University, Department of Economics, 2023)
This paper presents a new framework for analyzing automation, robotics, and hightech, which differs from the canonical model of technological progress by incorporating the higher education system. The main difference is that there is not just one type of skilled workers, but two types, and there is not one type of education but two - elite universities and standard ones. The gap between these two types of education is called "elitism gap". The "elitism gap" in the higher-education sector enables a separation of individuals by their abilities. Since the economy is divided between low-tech and high-tech sectors, the elitism gap leads to a separating equilibrium in which, high-ability workers graduating from top universities work in the high-tech sector, while lowability workers, graduate from standard universities and work in the low-tech industries. In consequence, human capital in both industries is different, which leads to wage inequality. We then analyze the effects of an increased use of robotics on inequality. We show that robots affect the "matching effect" between abilities and education, and in consequence, inequality increases. We also show that wages and productivity gaps between high-tech and low-tech sectors are fueled by the elitism gap in higher education. This leads to heterogeneity in human capital, and therefore to an increase in wage inequality. We develop an index of the elitism gap, and show a positive correlation between the index of elitism gap and inequality in OECD countries.
Keywords: I26; J24; O14; O4; 330; ability; skills; productivity; duality; higher education; robots; wage premium; international leadership